THE IMPACT OF COUNTRY-OF-ORIGIN, BRAND IMAGE, ATTITUDE TOWARD THE BRAND IMAGE ON CONSUMERS’ PURCHASE INTENTION IN INDONESIAN MARKET: A CASE STUDY OF HUAWEI SMARTPHONE IN JABODETABEK - Kewell Chung Kwok Zhong; Pauline H. Pattyranie Tan (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to examine the influence of Country of Origin (COO), Brand Image, and Attitude toward the Brand on Purchase Intention toward Huawei smartphones in Indonesia. The rapid development of the smartphone industry in Indonesia has intensified competition among global brands, making consumer perception a crucial determinant of purchasing behaviour. This research adopts a quantitative approach using purposive sampling with a total of 200 respondents who are familiar with Huawei smartphones. Data were collected through structured questionnaires using a 5-point Likert scale and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings indicate that Country of Origin has a significant positive effect on Brand Image, Attitude toward the Brand, and Purchase Intention. However, Brand Image does not significantly influence Purchase Intention directly. Meanwhile, Attitude toward the Brand has a strong and significant effect on Purchase Intention. These results highlight that consumer attitudes play a crucial mediating role in shaping purchase intention. The study contributes to the literature on consumer behavior and provides managerial insights for global brands in managing country-of-origin perception.